Epistemic cultures, knowledge cultures and the transition of agricultural expertise: Rural development in Tajikistan, Uzbekistan and Georgia - Kristof Van Assche; Anna-Katharina Hornidge; Anastasiya Shtaltovna; Hafiz Boboyorov (University of Bonn, Center for Development Research (ZEF), 2013)
In this paper, we investigate the utility of Knorr-Cetina's theory of epistemic cultures and knowledge cultures for the analysis of rural transition in post-socialist countries. We look at the evolution of agricultural expertise in Tajikistan, Uzbekistan and Georgia, with a special interest in the reconstruction of 'extension', a concept we also critically investigate by means of Knorr-Cetina's framework. It is argued that rural transition in the three countries is marked by patterns of convergence and divergence, and that each path can be described as a unique and interdependent combination of epistemic cultures and knowledge culture, leading to unique modes of interpretation, recombination and implementation of both imported and pre-existing models of extension.
Keywords: 330; rural development; Central Asia; extension services; knowledge; epistemic cultures